Removal of Orthophosphate by Adsorption onto Activaed Magnesium Oxide in Aqueous Solution - Xie, Fa-Zhi; Liu, Gui-Jian; Wu, Feng-Chang; Li, Guo-Lian; Zhu, Yuan-Rong (Asian Journal of Chemistry, 2012)
In this study, the adsorption properties of an activated magnesium oxide powders via precipitation method for orthophosphate was examined. The effect of different parameters such as pH, contact time, adsorbate concentration and temperature was investigated. The adsorption kinetics data were best described by the pseudo-second-order rate equation and equilibrium was achieved after 40 min. The adsorption isotherm of the activated MgO was approximated by a Langmuir type and the maximum adsorption capacity was 95.24 mg/g. The thermodynamic parameters like DG, DH and DS for the adsorption of phosphate ions have been evaluated and it has been found that the reaction was spontaneous and endothermic in nature.